The Effectiveness of Bibliotherapy to Improve Subjective Well-Being among Adolescents Living in Islamic Boarding Schools in a Rural District of Indonesia - Mulyadi, Andi; Asniar, Asniar; Tahlil, Teuku (Rifa'Institute, 2025)
Introduction: Adolescence is a critical developmental stage marked by significant emotional, cognitive, and social changes, during which individuals begin to form their identity and long-term psychological patterns. Objective: This study investigates the effectiveness of bibliotherapy as a psychological intervention to enhance subjective well-being (SWB) in adolescents living in dayahs in Aceh Besar. Methods: This quasi-experimental study employed a one-group pre-test and post-test design involving 61 adolescent students with low levels of subjective well-being (SWB). Data were collected using validated Indonesian versions of the Satisfaction with Life Scale (SWLS) and the Scale of Positive and Negative Experiences (SPANE), and analyzed using paired-sample t-tests. Results and Discussion: The results revealed statistically significant improvements in overall subjective well-being (SWB) (p = 0.001), life satisfaction (p = 0.001), positive affect (p < 0.001), and a reduction in negative affect (p = 0.001). These findings demonstrate that bibliotherapy is a practical, low-cost, flexible intervention that can be implemented by nurses, educators, or librarians within school or community settings. Conclusion: It offers a practical approach to promoting emotional balance and enhancing life satisfaction among adolescents, particularly those in resource-limited boarding school environments. This study highlights the importance of integrating bibliotherapy into adolescent health programs, particularly in religious educational settings, to enhance psychological well-being and promote resilient youth.